Effect of temperature on the metabolism, behaviour and oxygen requirements of Sparus aurata - M Remen (Inter-Research, 2015)
We investigated the effect of temperature on the limiting oxygen saturation (LOS) of gilthead sea bream Sparus aurata. This threshold was defined as the % O2 saturation where fish no longer upheld their routine metabolic rate (RMR, the metabolic rate of fed and active fish) during a progressive decline in oxygen saturation. S. aurata (398 ± 10 g, mean ± SE) were kept in 3 replicate tanks and subjected to 3 changes in temperature: 16 to 20°C, 20 to 16°C and 16 to 12°C. At each temperature, fish were left to acclimatize for 8 to 10 d, before daily feed intake (DFI), the routine oxygen consumption rate (routine MO2, mg kg-1 min-1) and the LOS were measured. In addition, at 20°C the swimming speed was measured in fish subjected to a decline in O2 from full air saturation to levels below the LOS (minimum of 8-10% O2). For the temperature range tested (12-20°C), DFI, MO2 and LOS increased exponentially with temperature (7.5-, 3.6- and 2.2-fold, respectively) with mean (± SE) LOS being 17 ± 1, 21 ± 0 and 35 ± 5% O2 at 12, 16 and 20°C, respectively. A gradual decline in swimming activity was observed as O2 declined below the LOS, indicating increasing metabolic stress and/or a ‘sit-out’ coping strategy which may prolong survival time in severe hypoxia. The results show the importance of temperature as an influential variable over the environmental O2 requirements of S. aurata.